Medico-Legal Profile of Domestic Accidental Fatalities: An Autopsy Based Study at SMS Medical College, Jaipur, Rajasthan - Surya Bhan Kushwaha; R.K. Punia; Shweta Goel (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Domestic accidents are a rising cause of death and injury, especially in low and middle-income countries like India. Many homes are not built with safety in mind, which increases the risk of accidents. These incidents can lead to serious injuries or death, often affecting vulnerable groups like children, the elderly, and people engaged in household activities. Aim: To examine the causes and patterns of domestic accidental deaths through autopsy𿿿ndings at SMS Medical College, Jaipur. Methodology: This descriptive, cross-sectional study was carried out from November 2023 to October 2024 in the Mortuary of the Department of Forensic Medicine & Toxicology, SMS Medical College, Jaipur. A total of 200 domestic accidental death cases were selected using systematic random sampling. Information was collected from inquest reports, police documents, and relatives of the deceased. A structured form was used to record details such as age, gender, accident type, time and place of occurrence, and cause of death noted during autopsy. Observation & Results: Adults made up the largest group of victims (42%), followed by elderly individuals (23%) and toddlers (18.5%). Most victims were male (60%). The leading cause of death was falling from a height (47%), followed by burns (29%) and slipping (8.5%). Most accidents occurred on Saturdays and during daytime hours, especially in the afternoon (35.5%) and morning (35%). Terraces (27%) were the most common location for fatal incidents. Shock was the most frequent medical cause of death (66.5%), followed by coma (35.5%). Conclusion: Domestic accidental deaths mainly affected adults and males, with falls and burns as the primary causes. Accidents mostly occurred during the day and on weekends. The study highlights the importance of home safety improvements, community education, and timely emergency care to reduce preventable deaths at home.